Phytochemical Screening and Evaluation of Various Extracts of Thespesia populnea for Antioxidant Activity - Banjare, Laxmi (International Journal of Pharmaceutical & Biological Archive, 2012)
Phytochemical Screening and Evaluation of Various Extracts of Thespesia populnea for Antioxidant Activity